СТРАТЕГІЯ МАКРОЕКОНОМІЧНОГО РОЗВИТКУ УКРАЇНИ В УМОВАХ БОРГОВОЇ КРИЗИ: ДОСВІД, ТЕОРІЯ ТА ПРАКТИКА - Lynnyk, O.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2016)
In the article different approaches to the definition of economic development were examined with the modern strategies being viewed. The current economic situation is described with the positive results of implemented reforms being estimated, the obstacles being defined and basics, which can contribute to the economic growth and development being formulated. REFERENCES1. Feldman M. et al (2015), The logic of economic development: A definition and model for investment, SAGE Journals, London, available at: http://epc.sagepub.com/content/early/2015/11/08/0263774X15614653 (Accessed 11 June 2016).2. Kozak J.G (ed.) (2009), Mizhnarodni stratehiyi ekonomichnoho rozvytku [International strategies of economic development], Centre for educational literature, Kyiv, Ukraine.3. Lin J. (2009), Economic development and transition: thought, strategy, and viability, Cambridge University Press, Cambridge,MA. https://doi.org/10.1017/CBO97805118056224. Acemoglu D. (2008), Introduction to modern economic growth, Princeton University Press, Princeton, NJ.5. Bruno R.L. et al. (2015), Technology Choices and Growth: Testing New Structural Economics in Transition Economies, Journal of Economic Policy Reform, vol. 18, part 2, pp. 131—152. https://doi.org/10.1080/17487870.2015.10135416. Kas’yanenko V.O. (2011), Zarubizhnyy dosvid upravlinnya innovatsiynym potentsialom ekonomiky ta mozhlyvosti yoho vykorystannya v Ukrayini [Foreign experience of economy’s innovational capacity management and the opportunities of its use in Ukraine], Marketyng i menedzhment innovacij [Marketing and management of innovations], vol. 4., part. 2, pp. 200-204.7. Moyseyenko I. And Fleychuk M. (2012), Stratehiya ekonomichnoho rozvytku Ukrayiny v umovakh kryzy [The strategy of economic development of Ukraine under conditions of the crisis], Byuleten Mizhnarodnogo Nobelivs`kogo ekonomichnogo forumu [The bulletin of international nobel economic forum], vol. 1, pp. 274-282.8. Pop-Eleches G. (2008), From Economic Crisis to Reform: IMF Programs in Latin America and Eastern Europe, Princeton University Press, Princeton, NJ. https://doi.org/10.1515/97814008355469. Swan W. (2014), Budget speech, Budget 2010–11, Commonwealth of Australia, Canberra, available at: www.budget.gov.au (Accessed 11 June 2016).10. Christie T. (2014), The Effect Of Government Spending On Economic Growth: Testing The Non-Linear Hypo thesis, Bulletin of Economic Research, vol. 66, pp. 183-204.11. Buffie E., Berg A., Pattillo C., Portillo R. and Zanna L.-F. (2012), Public Investment, Growth and Debt Sustai nability: Putting Together the Pieces, IMF Working Paper No. WP/12/144, Washington, USA.12. Tsina derzhavy [Price of the state] (2015), Expenditure, available at: http://costua.com/budget/expenditure/ (Accessed 11 June 2016).13. Eurostat (2015), available at: http://ec.europa.eu/eurostat/ (Accessed 11 June 2016).14. Onufryk M. (2016), Pensiynakryzadoviry [Pensioncrisis of trust], Mirror of the week, 3 March 2016, available at: http://gazeta.dt.ua/finances/pensiyna-kriza-doviri-_.html (Accessed 11 June 2016).